Arthroderma chiloniense sp. nov. isolated from human stratum corneum: Description of a new Arthroderma species. Issue 1 (18th October 2018) - Brasch, Jochen; Beck‐Jendroschek, Vera; Voss, Karin; Yurkov, Andrey; Gräser, Yvonne
Summary: A 68‐year‐old woman was submitted to our hospital because of erythematous and scaly skin lesions. To exclude tinea samples of stratum corneum were collected and used for mycological investigations. In this material, no fungal elements were detected microscopically, but inoculation on Sabouraud agar with cycloheximide yielded a presumptive dermatophyte fungus. Subsequent detailed investigations with conventional morphological and physiological methods and a phylogenetic analysis of the combined LSU rRNA gene (D1/D2 domains) and ITS region sequences suggested that the fungus represents a hitherto undescribed species of the genus Arthroderma . Here, we describe this species as Arthroderma chiloniense sp. nov., EMBL accession no. LT992885. This new species can be distinguished from phylogenetically related Arthroderma species using ribosomal ITS and LSU genes, and 60S L10 protein sequences; specific macroscopic, microscopic and physiological features are lacking. Our attempts to re‐isolate this fungus from the patient's skin failed although her skin lesions persisted. Most likely A. chiloniense is a geophilic species that incidentally contaminated or transiently colonised the patient's skin. To avoid diagnostic misinterpretations, it is necessary to distinguish A. chiloniense from truly pathogenic dermatophytes like Trichophyton ( T .) rubrum and T. interdigitale which can easily be confused with A. chiloniense based on similar mycelium morphology.